2008
DOI: 10.1007/s10620-008-0225-y
|View full text |Cite
|
Sign up to set email alerts
|

JAK2V617F Mutation in Patients with Portal Vein Thrombosis

Abstract: In a retrospective cohort, we investigated the presence of the JAK2V617F mutation in chronic non-cirrhotic portal vein thrombosis (PVT) patients, irrespective of the presence or absence of myeloproliferative diseases (MPDs). We identified 25 patients in whom thrombophilia workup was completed. The diagnoses of MPDs were made according to the World Health Organization (WHO) criteria. JAK2V617F mutation analysis was performed by allele-specific polymerase chain reaction (PCR). There were 9 male and 16 female pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Twenty-four studies were therefore included in this systematic review. 10,21,23,25,27,30,33,37,[40][41][42][43][44][45][46][47][48][49]51,52 Interobserver agreement for study selection was excellent ( ϭ 0.96).…”
Section: Study Identification and Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-four studies were therefore included in this systematic review. 10,21,23,25,27,30,33,37,[40][41][42][43][44][45][46][47][48][49]51,52 Interobserver agreement for study selection was excellent ( ϭ 0.96).…”
Section: Study Identification and Selectionmentioning
confidence: 99%
“…Studies ranged in size from 11 to 560 patients; a total of 3508 patients were included. Six case-control studies 10,23,25,27,35,40 and 18 retrospective cohort studies 21,24,30,31,34,36,37,[41][42][43][44][45][46][47][48][49]51,52 were included in our systematic review. Five studies enrolled patients consecutively.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have focused on the prevalence of JAK2 V617F mutation in patients with venous thrombosis. In patients with splanchnic vein thrombosis and without overt MPN, JAK2 V617F positivity has ranged from 12 to 74% [7,8,9,10,11,12,13,14,15,16] with a mean prevalence of 32.7% [17]. This wide range of JAK2 mutation positivity could be explained by several factors, including heterogeneity in the inclusion criteria, small sample size, different sensitivities of the assays employed for the detection of the mutation, and the different types of biological samples used [18].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that JAK2 (V617F) mutation is present in 50-79.3 % all cases of diagnosed MPN with SVT. On the other hand, in patients with latent MPN with SVT, the incidence of JAK2 (V617F) mutation varies from 11 to 74 % [13][14][15][16][17][18][19][20][21][22][23]. Only one retrospective study reported a low prevalence rate of 9.3 % [24].…”
Section: Jak2 (V617f) Mutation Myeloproliferative Neoplasms and Splementioning
confidence: 99%